Simple Rules, Templates, and Heuristics! An Attempt to Deconstruct the Craft of Writing an Entrepreneurship Paper. (May 2020) - Shepherd, Dean A.; Wiklund, Johan
Although there are a number of excellent suggestions from editors on how to conduct, structure, and publish research in general, we thought it would be useful to offer some guidance from an entrepreneurship perspective. Writing this paper allowed us to reflect on our work as authors, reviewers, and editors to offer some advice in the form of simple rules for conducting entrepreneurship research, templates for structuring entrepreneurship research, and heuristics for writing entrepreneurship research. While not exhaustive, we have focused on the "rules of thumb" that have served us well and we hope that others find them useful.